National standards and school reform in Japan and the United States - DeCoker, Gary. (New York : Teachers College Press, 2002)
DeCoker and his colleagues explore the implications of a national U.S. curriculum through the study of Japanese education. The authors suggest that the U.S. educational system lacks certain organizational mechanisms that support student achievement and would facilitate teacher involvement in the educational reform process. Presenting important implications for American education, this volume features: a comprehensive look at national standards in Japan, from their development at the Ministry of Education to their implementation in the classroom; detailed descriptions and intriguing analyses of education policy, textbooks and other curricular materials, professional development, and the relationship between the public and private sectors in Japan and the United States; an epilogue by Thomas Rohlen containing his analysis of educational reform efforts in both countries, his description of the symbiotic relationship between the two educational systems, and his predictions for the future of public education as technological change and global market capitalism extend private sector initiatives beyond national borders.
Introduction. What do national standards really mean? / Gary DeCoker -- The development of the Course of study and the structure of educational reform in Japan / Hiroshi Azuma -- Setting national standards : educational reform, social change, and political conflict / Gerald K. LeTendre -- How do Japanese and U.S. elementary science textbooks differ? : Depth, breadth, and organization of selected physical science units / Ineko Tsuchida and Catherine C. Lewis -- The creation of Japanese and U.S. elementary science textbooks : different processes, different outcomes / Catherine C. Lewis, Ineko Tsuchida and Samuel Coleman -- Comparing Japanese and U.S. teachers' manuals : implications for mathematics teaching and learning / Shin-ying Lee and Akane Zusho -- Individual differences and Japan's Course of study / Harold W. Stevenson -- Teacher professional development in Japan / Nobuo K. Shimahara -- "It's glacial" : incrementalism and Japan's reform of foreign language education / David L. McConnell -- Deregulating Japan's high school curriculum : the unintended consequences of educational reform / Gary DeCoker -- The role of the private sector in determining national standards : how juku undermine Japanese educational authority / Nancy Ukai Russell -- Epilogue. Concluding observations : wider contexts and future issues / Thomas P. Rohlen.
Includes bibliographical references and index.
Keywords: Education -- Standards -- Japan; Education -- Standards -- United States; Curriculum change -- Japan; Curriculum change -- United States; Comparative education